The influence of trkB deficiency on long-term outcome of peripheral nerve injury in mice - Kotulska, Katarzyna; Larysz-Brysz, Magdalena; Marcol, Wiesław; Jóźwiak, Jarosław; Grajkowska, Wiesława; Lewin-Kowalik, Joanna (Folia Neuropathologica, 2007)
The long-term outcome of peripheral nerve injury is often unsatisfactory, especially if the injury resulted in a gap between transected nerve stumps. Brain-derived neurotrophic factor and its receptor, trkB, are strongly implicated in the early phase of axonal regeneration after injury. We examined the role of trkB in long-term functional and morphological outcome of peripheral nerve injury. The sciatic nerve was transected in wild-type and heterozygous trkB-deficient mice. The nerve was either left cut or immediately sewn up or the gap injury model was performed. The gap was provided with autologous or cross (obtained from other genetic group) graft. Sciatic nerve function as well as autotomy was assessed during 16-week follow-up. The long-term functional outcome of nerve cut or immediately rejoined did not differ between wild-type and trkB-deficient mice. Gap injury provided with nerve graft resulted in better functional outcome in trkB-deficient mice than wild-type animals. Sixteen weeks after the surgery, the animals were sacrificed and histological evaluations were performed. The number of nerve fibres regenerating into the distal stump of transected and rejoined nerves did not differ between wild-type and trkB-deficient animals. TrkB deficiency markedly increased the number of Schwann cells as well as mast cells at the injury site and in the distal stump of the regenerating nerve. TrkB deficient nerves also showed higher expression of bcl-2 protein but lower of trkA and NGF than wild-type ones. Our results show for the first time the possible deleterious role of trkB receptor in long-term outcome of peripheral nerve injury.